Histórico familiar de mulheres encarceradas: fatores de risco e proteção para os filhos - Ormeño, Gabriela Isabel Reyes (Universidade Federal de São Carlos, 2013)
This dissertation was developed in the form a group of scientific papers which are interconnected in order to describe the main risk and protective factors experienced by incarcerated mothers and their children. Initially there was a systematic review of the Brazilian literature of dissertations, thesis and papers, with the theme of incarcerated women, indicating lack of continuity of studies and the need for intervention programs with greater methodological rigor involving the women and families. Secondly e reviewed the Brazilian and international literature on main characteristics of children of incarcerated womem, signaling the need for systematic research in the context of primary prevention for these children. The history of violence experienced by these women in childhood and adulthood, found the occurrence of child maltreatment, high rate of attempted suicide, intimate partner and violence victimization, a high similarity of Brazilian with the data described in the international literature. Major traumatic situations described by incarcerated women with respect to their children, indicate thus these children were exposed to intimate partner violence, and child abuse suffered as a form of discipline. Incarcerated mothers maintained ties with their children through letters or visits from their offspring to care for their children after serving their sentences. The birthrate in the mother lives of these women included a large number of pregnancies, and children, as well as lack of family planning, pointing to the neglect from the Health systems and the prison in understanding the needs experienced by this population. The parenting style received in childhood by their caregivers was also analyzed from the perception of the female prisoners, as well as the parenting style used by themselves with their own children before incarceration, showing the intergenerationality of parenting practices. By analyzing interlinked variables in the lives of incarcerated women such the history of child maltreatment of the women and family violence history we conclude the need for prevention programs to work with women in situation of incarceration, as well as with the children of these women in order to prevent intergenerational violence. It is hoped that this dissertation will subsidy the creation of public policies addressing the many risks by incarceration women and their children.
Family history of incarcerated women: Risk factors and protection for children
Keywords: Psicologia; Encarceramento; Fatores de risco e proteção; Mulheres prisioneiras; Filhos de prisioneiros; Fatores de risco e proteção ao encarceramento; Mulheres encarceradas; Filhos de encarcerados; Risk factors and protection to incarceration; Incarcerated women; Children of incarcerated women; CIENCIAS HUMANAS::PSICOLOGIA